Future IPM Trends in Trinidad and Tobago: A Qualitative Study of Farmers’ Perspectives - Thomas J Wynn; Ricky H Coppedge; Robert Strong (Journal of International Agricultural and Extension Education, 2013)
Agriculture plays a fundamental role in the infrastructure of many developing economies. Trinidad and Tobago depends on food imports for over 90% of its domestic food supply making agriculture a politically sensitive sector. Technology adoption, specifically Integrated Pest Management (IPM), is one method used by the government to help enhance food security. The purpose of this study is to evaluate factors affecting IPM program adoption in Trinidad and Tobago, to describe current practices used by farmers, and to identify future perceptions of IPM technology. The theoretical framework for this study was constructed using Rogers’ diffusion of innovations as it pertains to agriculture. Twenty-one farmers were purposively selected to participate in this study. Economics, progressive ideology, mixed control methods, pest management practices, traditions, and a holistic approach to agriculture were identified as the key elements of IPM programs by farmers. Practitioners seeking to influence the adoption of IPM in this country should be knowledgeable of IPM program elements. Future research should seek to enhance information communication and dissemination.
Keywords: Diffusion of Innovations; Integrated Pest Management; Small Scale Farmers’ Perceptions